Subcultural Differences in Processing Social and Non-social Positive Emotions Between Han and Uygur Chinese: An ERP Study - Deng, Xinmei; You, Yuanyuan; Sai, Liyang (Frontiers in Psychology, 2019)
While previous studies have shown that East-West cultural differences exist in processing different emotional stimuli, potential subcultural differences within a large cultural group are not well understood. In this study, we examined subcultural differences in the event-related potential (ERP) modulations in the brain, during processing social-positive and nonsocial-positive stimuli among 21 Han Chinese and 21 Uygur Chinese. Results showed that the magnitudes of P2, N2 and LPP were larger in Uygur Chinese than in Han Chinese. For social-positive stimuli, the P2 and LPP 300-600 were larger in Uygur Chinese than in Han Chinese. However, there was no significant difference in nonsocial-positive stimuli. These results indicated that social-positive emotions were more prioritized in emotional processing among Uygur Chinese than Han Chinese. These findings contribute to the growing literature on subcultural differences in processing different types of positive stimuli.